(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article scientifically substantiates the physiological foundations of sanitaryand hygienic conditions in classrooms. The study analyzes the impact of theeducational environment on students’ bodies, particularly on the functioning ofthe visual, auditory, respiratory, and nervous systems. The importance ofcompliance with physiological standards for lighting, temperature, humidity, airexchange, noise levels, furniture, and sitting posture in classrooms is justified inrelation to maintaining students’ work capacity, attention, and health. In addition,the paper addresses issues related to the prevention of fatigue, visual strain, spinaldisorders, and functional impairments that arise as a result of noncompliance withsanitary and hygienic requirements. Scientific conclusions and practicalrecommendations for creating a healthy and comfortable educationalenvironment in classrooms are presented.